On the other side of the Lacanian mirror: translating translingual literature with the author - Branca, Gloria (Traduttologia e Traduzioni, vol. III: Interdisciplinarietà della traduzione, 2021)
This article aims at investigating the effectiveness of some psychoanalytic notions in the area of translingual literary translation by analysing a corpus of paratexts concerning the relationship between the Romanian philosopher Emil Cioran and his Italian translator, Mario Andrea Rigoni. Jacques Lacan’s key concepts of mirror stage and object lack are introduced to highlight the intersubjective dynamics occurring between the two subjects, namely the author and the translator involved in the engaging challenge of translating the language of exile.